Systematics, morphology and ecology of rails (Aves: Rallidae) of the Mascarene Islands, with one new species - Hume, Julian Pender (Zootaxa, 2019)
Five species in five genera of extinct endemic rails have been described from the Mascarene Islands of Mauritius, Réunion and Rodrigues: the Mauritian Red Rail or Poule Rouge Aphanapteryx bonasia; Mascarene Coot or Poule d’eau Fulica newtonii; which occurred on Mauritius and Réunion; Réunion Wood Rail Dryolimnas augusti; Réunion Gallinule or Oiseaux bleu ‘Porphyrio caerulescens’; and Rodrigues or Leguat’s Rail Erythromachus leguati. All are known from fossil remains and/or from contemporary accounts and illustrations. A sixth species of rail Dryolimnas sp. nov. is described herein from fossils from Mauritius, but was not unequivocally previously reported in the contemporary literature. This paper provides an analysis of the Rallidae of the Mascarene Islands based on existing and newly discovered fossil remains, and details historical reports and accounts. Comprehensive osteological descriptions and synonymies are also included. Their ecology and extinction chronologies are interpreted from historical evidence. The relationships of Aphanapteryx and Erythromachus are unresolved, having clearly been isolated for a considerable time; the middle Miocene is the earliest their ancestors could have arrived on the Mascarenes, but this may have happened more recently. Mascarene derivatives of Fulica, Porphyrio and Dryolimnas are of much more recent origin, and appear to have originated in Africa or Madagascar. All terrestrial rails on Mauritius, Réunion and Rodrigues, were probable victims of cat predation following their historic introduction to the islands, whereas over-hunting by humans was probably the primary cause of extinction of ‘Porphyrio caerulescens’ on Réunion. The only extant rail on the Mascarenes today, the Madagascar race of Eurasian Moorhen Gallinula chloropus pyrrhorrhoa, is a recent arrival, having colonised Mauritius and Réunion after the extinction of Fulica newtonii.